Recent Progress in European Advanced Therapy Medicinal Products and Beyond - Yu, Tracy T. L.; Gupta, Pravesh; Ronfard, Vincent; Vertès, Alain A.; Bayon, Yves (Frontiers in Bioengineering and Biotechnology, 2018)
Cell- and gene-based therapies form one of the pillars of regenerative medicine. They have the potential to transform quality of life and improve the health status of patients with genetic and cellular defects, including genetic diseases, neurodegenerative diseases and tissue malignancies, amongst others. Despite numerous challenges, in the last decade, tremendous unified efforts by research and clinical scientists in academic, translational and industry settings have resulted in tangible outcomes in the form of many marketing authorisations and approved commercial firsts, such as Glybera®, Kymriah®, YESCARTA®, Holoclar® and Luxturna™. This report presents a succinct analysis of developments in the regenerative medicine landscape, including immuno-oncology, with a focus on the European Union and examples of clinical and commercial successes and failures. The factors that led to these exciting developments in immune-oncology are also considered. Concurrently, several key issues, spanning from the identification of unmet clinical need, associated challenges, economic evaluation to policy improvements are emphasised. Furthermore, industry insights encompassing the five-dimensional research and development framework for the focused development of medicine, pricing and reimbursement issues, technology adoption and permeation of innovative advanced therapy medicinal products in the clinical set up are reflected upon, following elaborate discussions that transpired in different thematic tracks of Tissue Engineering & Regenerative Medicine International Society European Chapter 2017 Industry Symposium.